Perlindungan Hukum Terhadap Hak Tenaga Kerja Pada Perjanjian Kerja Outsourcing - Fauzan azima faturachman; Maudy anjani; Raihan heryadi; Tomi J.E hutasoit; Vasco javarison zacharias; Mustika mega wijaya (JOURNAL SAINS STUDENT RESEARCH, 2024)
Along with the increasingly rapid development of the world of business and technology in Indonesia, the need for labor is also increasing. Many companies practice outsourcing, in order to reduce the number of workers and gain greater profits by handing over the responsibility of supporting work to other companies. Outsourcing is the procurement of labor services carried out by a company. Technically, a company provides workers with certain competencies to be employed in other companies. With the aim of carrying out tasks that are not related to core work. Outsourced workers are part of the workforce that is regulated and protected through Law Number 13 of 2003 concerning Employment. Regulations regarding outsourcing have been stipulated in the Employment Law Article 64, Article 65 and Article 66, Constitutional Court Decision No.27/PUU-IX/2011. Problems that often occur in the outsourcing system are unilateral termination of employment, the rights of outsourced workers are not guaranteed, and there is no guarantee of continuity of work provided by the company. Based on this reality, the general aim of this research is to find out problems regarding the implementation of legal protection given to outsourced workers in Indonesia. The type of research is normative juridical. The approach method used is a statutory and conceptual approach. The data source used is secondary data. Data analysis was carried out descriptively qualitatively. The research results show that the weak legal system in Indonesia and lack of supervision from the government has resulted in many companies violating the rights of workers or outsourced workers, especially regarding legal protection. Because for them, protection is really needed for workers or outsourced workers